Relationship Between T-Cell Exosomes and Cellular Subsets in SLE According to Type I IFN-Signaling - López, Patricia; Rodríguez-Carrio, Javier; Caminal-Montero, Luis; Suárez, Ana (Frontiers in Medicine, 2020)
Objective: To quantify the levels of circulating exosomes derived from T-cells and monocytes and their possible associations with leukocyte subpopulations and cytokine milieu in Systemic Lupus Erythematosus (SLE). Methods: Total circulating exosomes (CD9+-Ex) and those derived from T-cells (CD3+-Ex) and monocytes (CD14+-Ex) were quantified by flow cytometry in 82 SLE patients and 32 controls. Leukocyte subsets and serum cytokines were analyzed by flow cytometry or by immunoassays. IFN-score was evaluated by real time RT-PCR in whole blood samples from a subgroup of 73 patients and 24 controls. Results: Activation markers (IFNR1 and BLyS) on monocytes, neutrophils and B-cells correlated inversely with circulating exosomes (CD9+-Ex, CD3+-Ex and CD14+-Ex) in controls but directly with CD3+-Ex in patients (all p<0.05). Although CD9+-Ex were increased in SLE, no differences were found in CD3+-Ex, supporting that exosome content accounts for this opposite role. Interestingly, CD4+CD28null cells correlated with CD3+-Ex in patients and controls, and displayed similar associations with leukocyte subsets in both groups. Additionally, CD3+-Ex correlated in patients with the expression of CD25 in CD4+CD28null cells. Furthermore, the activated status of this senescent subset was related to IFNα serum levels in controls and to IFN-score in SLE patients. Finally, patients presenting high IFN-score, in addition to elevated CD25+CD28null cells associated with the activation of myeloid cells, displayed higher levels of inflammatory cytokines and chemokines. Conclusion: Our results support a relationship between T-cell exosomes and cellular subsets in SLE according to type I IFN-signaling, which could amplify chronic immune activation and excessive cytokine/chemokine response.